Deficiencies in postoperative surveillance for veterans with gastrointestinal cancer. Issue 3 (16th December 2018) - Taylor, Lauren J.; Xu, Kerui; Maloney, James D.; Voils, Corrine I.; Weber, Sharon M.; Funk, Luke M.; Abbott, Daniel E.
Abstract : Background and Objectives: National guidelines for gastrointestinal (GI) cancers offer surveillance algorithms to facilitate detection of recurrent disease, yet adherence rates are unknown. We sought to characterize postoperative surveillance patterns for veterans with GI cancer at a tertiary care Veterans Affairs Hospital. Methods: A single‐center retrospective cohort study identified patients who underwent surgical resection for colorectal, gastroesophageal or hepatopancreaticobiliary malignancy from 2010‐2016. We calculated the annual rate of cancer‐directed clinic visits and abdominal imaging and used National Comprehensive Cancer Network guidelines as a benchmark by which to assess adequate surveillance. Results: Ninety‐seven patients met inclusion criteria. Median surveillance time was 1203 days. Overall, 44% of patients had insufficient surveillance. Specifically, 11% received no postoperative imaging and 7% had no cancer‐directed clinic visits. An additional 30% received less than recommended surveillance imaging and 12% attended fewer than recommended clinic visits. By disease site, insufficient imaging was most common for patients with hepatopancreaticobiliary cancer (63%), while inadequate clinic follow‐up was highest for colorectal cancer (24%). Conclusion: A significant proportion of veterans with GI cancer received either inadequate postoperative surveillance based on national guidelines. This deficiency represents an opportunity for improvement through targeted efforts, including telemedicine and education of patients and providers.